Análisis de la cadena logística de exportación de banano, de la empresa Agrorganica S.A de la provincia de El Oro. - Dominguez Pedreros, Erick Alexander (2018)
Foreign trade in the last 50 years has grown by leaps and bounds opening up the international exchange of goods, which meet the needs of different importing countries. To perform exports and imports of goods or services, it is essential to have logistics experts, who are responsible for moving loads from one place to another, ensuring that they arrive in perfect condition to their destination. Markets become competitive with the emergence of technology. The intensification of competitiveness has turned logistics into one of the fundamental keys of trade. The efficient development of logistics services facilitates the mobility of products, guaranteeing their safety, speed, as well as the reduction of their cost. Within the logistic process the passage through customs aes a very important stage since it is the entity in charge of the control of entry and exit of goods and trafficking of people in a country. Passing by physical and documentary formalities to give the approval of entry and exit of the primary zone. Customs through your office expedite the processes of international trade in goods. This paper analyzes the logistic process of exporting organic bananas from the company AGRORGANICA S.A in the province of El Oro, which is dedicated to the production and export of organic bananas. The banana production in Ecuador has been maintained in a positive way in the last ten years, it is the most important production at the country level, and it is also the largest exporter of bananas worldwide. It describes the importance of logistics and the different means of transport to be used internally and externally, the use of Incoterms ('International Trade Terms'), during the logistics route, assuming their responsibilities as stipulated in the negotiation clause. When talking about transport in logistics is talking about the movement of cargo in all its known forms: air, sea and land, through which inputs are transferred, raw materials and finished products from one point to another according to a demand planning. The methodology used in this case analysis is qualitative, descriptive, and bibliographic based on scientific articles of indexed journals that serve as support for the information provided. The banana export logistic chain is born from the moment the fruit is cut to its destination abroad, the cold chain is the main thing to keep fruit in perfect condition, this you know from the products to the exporter and importer, it is for this reason that in the different processes its temperature is considered during the packing, sealing, internal and international transport, loading and unloading of the fruit. The company has an efficient logistics chain, which complies with the requirement of the transportation of the fruit from its country of origin, Ecuador, Port of Contecon S.A city of Guayaquil, to the United States, Philadelphia Port and destination city. When defining its competitive strategy, the company must identify the generators of costs and value in its processes. Hence, an important aspect is to identify the value chain and direct all necessary actions for it’s strengthening, through the integral logistics, logistic strategies used by the company are constantly monitored the load from the farm to the port of destination through its satellite system.